Pengembangan Media Pembelajaran Video Animasi 2D Berbantuan Canva pada Materi Berteman dalam Keberagaman Mata Pelajaran Bahasa Indonesia Kelas 2 SDN 2 Tiudan Kabupaten Tulungagung - Putri, Adelia Ayu Permata; Anny, Ammy Aulia Renata; Astutik, Leny Suryaning (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Indonesian language learning for the topic of Friendship in Diversity in grade 2 of elementary school is still dominated by lecture methods and the use of books, so that learning tends to be monotonous and less interesting for students. This condition is the basis for the development of 2D animated video media assisted by Canva. This study aims to develop valid and practical media to support the learning of this material. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of media experts, material experts, linguists, teachers, and grade 2 elementary school students. Data were collected through validation sheets and response questionnaires, then analyzed descriptively quantitatively using percentages. The results showed a validity level of 92% from media experts, 97% from material experts, and 96% from linguists. The practicality of the media reached 90.5% in small group trials, 98.2% in field trials, and 98.3% based on teacher responses. Thus, the 2D animated video media assisted by Canva is declared very valid and very practical and can be an alternative interesting visual media to support Indonesian language learning in the material of Making Friends in Diversity in grade 2 of elementary school.